2021
DOI: 10.1007/s11695-021-05327-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy with Omentopexy: Is It Really a Promising Method?—A Systematic Review with Meta-analysis

Abstract: Purpose Laparoscopic sleeve gastrectomy (LSG) is one of the most commonly performed bariatric procedure worldwide. Omentopexy during LSG is a novel variation of this well-established technique. There are no clear conclusions on indications for this procedure, safeness, and effects of such a method. We aimed to compare the outcomes of laparoscopic sleeve gastrectomy (LSG) with omentopexy (OP) and without omentopexy. Materials and Methods We searched the Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…But in the length of hospital stay and postoperative morbidity, we have different ideas. 35 At the same time, the study is aware that our results have several limitations. First of all, the impact of various preoperative preparation, surgical techniques, surgical equipment, and postoperative care cannot be manipulated.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…But in the length of hospital stay and postoperative morbidity, we have different ideas. 35 At the same time, the study is aware that our results have several limitations. First of all, the impact of various preoperative preparation, surgical techniques, surgical equipment, and postoperative care cannot be manipulated.…”
Section: Discussionmentioning
confidence: 86%
“…They found a significant difference between LSG and Ome + LSG groups, indicating that Ome can reduce the incidence of gastric cancer leakage after LSG, which is the same as ours. But in the length of hospital stay and postoperative morbidity, we have different ideas 35 …”
Section: Discussionmentioning
confidence: 99%
“…Leaks remain the most important complication causing significant morbidity and mortality after LSG [ 27 ]. The surgeons made every effort to decrease the incidence of leaks, including omentopexy, staple-line reinforcement, oversewing suture, absorbable polymer membrane, or no reinforcement [ 28 ]. The development of a leak after LSG might result from ischemia in the gastric wall next to the staple line, stenosis of the sleeve, or increased intraluminal pressure related to low compliance of the gastric tube [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from staple line reinforcement, omentopexy is another type of reinforcement technique, which uses sutures to fix the rest of the stomach to the free edge of the greater omentum [21]. The effect of SG with omentopexy on the rate of postsurgery complications was investigated in 3 systematic reviews [22][23][24], which reported inconsistent results. Of the 3 reviews, 2 [22,24] suggested that SG with omentopexy outperforms SG without omentopexy in reducing gastrointestinal adverse reactions (eg, nausea, reflux, and vomiting), while in terms of reducing gastric leakage, they showed the opposite effects.…”
Section: Introductionmentioning
confidence: 99%